Towards a more inclusive applied linguistics: researches on the English teacher, autism and Assistive Technology - Araújo, Laryssa; Larre, Julia (The ESPecialist, 2022)
In recent decades, the presence of students with autism in regular schools has been more frequent. This fact is of interest to Applied Linguistics, since the area’s agenda consists of issues that are present in society. Thus, the objective of this research is to look for dissertations and theses referring to English teachers, autism spectrum disorder and Assistive Technology, in order to understand the national panorama in the field of Applied Linguistics. Therefore, a research in the CAPES Theses and Dissertations Catalog and in the Digital Library of Theses and Dissertations (BDTD) was carried out to select the data for this paper. This study is bibliographic and documentary, since the researches analyzed were already published. As results, there is little research on the English teacher and autism and when added to Assistive Technology, postgraduate research in the field of LA is more scarce in both repositories. Regarding the content of the research, the results show that most part of the courses that train English teachers do not encompass Autism Spectrum Disorder and Assistive Technology.